Diffuse alveolar hemorrhage in a child with mild hemophilia A who underwent bone marrow transplantation for thalassemia: a case report - Nguyen, Hoa Thi Kim; Faulkner, Lawrence; Bui, Son Binh Bao; Lederman, Henrique Manoel; Ho, Nhan Thi Thanh; Dang, Tam Thi (Frontiers in Hematology, 2025)
Diffuse alveolar hemorrhage (DAH) is a relatively rare complication of bone marrow transplantation (BMT) associated with a high risk of mortality. It generally occurs in the early post-transplant phase during severe thrombocytopenia; however, since most thrombocytopenic cases do not develop DAH, cofactors are at play. Here, we discuss the case of a 4-year-old male child with mild asymptomatic hemophilia A discovered on routine evaluation pre-BMT, who developed DAH after a fully matched sibling BMT for HbE/Beta-thalassemia. The patient presented on day +21 post-BMT with sudden onset of cough followed one day later by hemoptysis. He had received FVIII supplementation with PTT normalization and FVIII levels of 28%. A chest CT scan showed interstitial lung disease with areas of ground glass bilaterally, mainly in the lower lobes. A radiological diagnosis of DAH was made, and the child was treated with additional FVIII concentrate (Advate), blow-by oxygen supplementation, red blood cells transfusion, platelet transfusion, methylprednisolone, tranexamic acid, and antioxidants (vitamin C and E). He responded well and recovered in a few days. Mild hemophilia associated with DAH post-BMT has never been reported before, however, it should be considered as a potentially treatable cause of DAH after BMT. FVIII levels should be part of the routine workup of children developing DAH post-transplantation. In the presence of thrombocytopenia, high FVIII levels of >30-40% might be required to prevent/treat DAH.